Peningkatan Pengetahuan Model Praktik Keperawatan (MPKP) dan Standar Asuhan Keperawatan (SAK) pada Pelayanan Keperawatan - Riama Marlyn Sihombing; Peggy Sara Tahulending (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Management function, which consists of planning, organization, directing/actuating, controlling, is a cycle in the management process that cannot be separated). A manager does not only perform one management function but an entire function to ensure service quality. Based on the results of the study and discussion with the head of the nursing division at an Indonesian private hospital, it was found that most nurses did not understand the application of Professional Nursing Practice Models (MPKP) ward. The aim is to provide a proper understanding of professional nursing practice, how the process and what needs to be done by nursing practice, and a correct understanding of nursing care standards (SAK) that can be addressed as a result of evaluation in the form of documentation carried out by nurses by the SDKI, SIKI and SLKI standards. The method of implementation includes a pre-test, providing MPKP and SAK materials, and implementing post-tests. The results of the 49 nurses who attended showed that there was an increase in understanding (p 0.001). Further suggestions are expected to be carried out by training with demonstration methods, role-play, or case studies to increase cognitive, affective, and psychomotor knowledge.